Hubungan Pengetahuan dengan Kepatuhan Ibu Balita Melakukan Kunjungan Ke Posyandu di Wilayah Kerja Puskesmas Pucangsewu Kota Surabaya - Sabrina Anindya Anisafitri; Novera Herdiani; Kardita Puspa Monitasari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Efforts to minimize MMR and IMR are one of them by carrying out activities regarding health empowerment which are held by holding Posyandu in every village or region. Parents, especially mothers, who focus on Posyandu activities held by the Puskesmas on an ongoing basis will have a very important impact on providing effective interventions and positive experiences for mothers and toddlers. Posyandu is a place for health services in the community that can be accessed by all people. Socialization and prevention at Posyandu is highly expected, especially to improve nutritional status and to find solutions regarding maternal and child health. This type of quantitative research uses a cross-sectional approach. This research was conducted at the Pucang Sewu Health Center in Surabaya City in April 2023. The population and sample in this study were all mothers who had toddlers aged up to 5 years with a sample of 50 respondents. The research instrument was a questionnaire about the mother's knowledge of Posyandu and there were 2 agree and disagree categories. Data processing techniques for this study used statistical tests with the help of the SPSS application. The statistical test used for this study is the Spearman Correlation. This study shows that a p-value of 0.000 <0.05 is obtained, which means that there is a relationship between mother's knowledge about Posyandu and compliance with toddler mothers visiting Posyandu in the Working Area of ​​the Pucang Sewu Health Center, Surabaya City.